(untitled) (International Journal of Studies in Nursing, 2017)
Sense of community has four elements: 1) membership, 2) influence, 3) integration and fulfillment of needs, 4) shared emotional connection. It is a term often used in relation to a geographic location, as in a neighbourhood, town or region. However, the concept encompasses much more than location and is often extended to include the work environment and relationships people build with co-workers. Scant attention has been paid to developing and testing the construct among nursing communities. This study explores how a theoretical conceptualisation of sense of community applies to nurses; describes the development of the Nurse Sense of Community Index (NSCI), and reports the results of a survey (N = 672) of New Zealand nurses. Key findings relate to high membership and low influence subscale scores, low levels of sense of community among the youngest nurses, and high levels among those working in speciality areas (i.e., small, close-knit workplaces). In addressing these issues it is recommended that early-career nurses be placed in smaller sized workplaces or teams and that preceptor and mentor programmes be used to enhance the development of sense of community among mid-career nurses. Significantly, findings demonstrate the presence of a sense of community among nurses and provide evidence that the NSCI reliably measures the construct.